ANALISIS KINERJA INDUSTRI TPT INDONESIA - Ragimun, Ragimun (Jurnal Kajian Ekonomi dan Keuangan, 2010)
Textile industry can be categorized the oldest industry in Indonesia. This is a significant industry, which provides not only on economic contribution but also on absorbing employment for the total 15% of all manufacture sectors.At the present, textile industry is facing some structural problems, such as the high cost of energy, insufficient of infrastructure, the low technology and well- worn of the machines, and also the overflowing of China's textiles into Indonesia markets. Those are causing high cost of production and further impeding competitiveness of domestic textile in the world marketOn the early stage, the textile industry development was boosted by the Foreign Investment Law (1967) and the Domestic Investment Law (1968). In addition, the export quota system grows up steadily during the period of 1984 to 2000, which reach to 18, 5% per year. For the last 5 years, however, the export shows a fluctuation. For 2000, the number reaches US$ 8.3 billion, and in 2009 goes to US$ 9.26 billion or just a tiny increase of 3.41 % per year.